Tanzania's reptile biodiversity: Distribution, threats and climate change vulnerability. (December 2016) - Meng, Han; Carr, Jamie; Beraducci, Joe; Bowles, Phil; Branch, William R.; Capitani, Claudia; Chenga, Jumapili; Cox, Neil; Howell, Kim; Malonza, Patrick; Marchant, Rob; Mbilinyi, Boniface; et al.
Abstract: Assessments of biodiversity patterns and threats among African reptiles have lagged behind those of other vertebrate groups and regions. We report the first systematic assessment of the distribution, threat status, and climate change vulnerability for the reptiles of Tanzania. A total of 321 reptile species (including 90 Tanzanian endemics) were assessed using the global standard IUCN Red List methodology and 274 species were also assessed using the IUCN guidelines for climate change vulnerability. Patterns of species richness and threat assessment confirm the conservation importance of the Eastern Arc Mountains, as previously demonstrated for birds, mammals and amphibians. Lowland forests and savannah-woodland habitats also support important reptile assemblages. Protected area gap analysis shows that 116 species have less than 20% of their distribution ranges protected, among which 12 are unprotected, eight species are threatened and 54 are vulnerable to climate change. Tanzania's northern margins and drier central corridor support high numbers of climate vulnerable reptile species, together with the eastern African coastal forests and the region between Lake Victoria and Rwanda. This paper fills a major gap in our understanding of the distribution and threats facing Tanzania's reptiles, and demonstrates more broadly that the explicit integration of climate change vulnerability in Red Listing criteria may revise spatial priorities for conservation. Highlights: Conservation importance of Eastern Arc Mountains is reconfirmed for reptiles. Top two threat categories: Agriculture & aquaculture and biological resource use 116 reptile species have less than 20% of their distribution ranges protected. 31–91% of reptile species assessed climate change vulnerable in all scenarios. Localities for non-climate and climate threatened species are not congruent.